Lessons learnt running distributed and remote mixed reality experiments - Steed, Anthony; Archer, Daniel; Brandstätter, Klara; Congdon, Ben J.; Friston, Sebastian; Ganapathi, Priya; Giunchi, Daniele; Izzouzi, Lisa; Park, Gun Woo (Warren); Swapp, David; Thiel, Felix J. (Frontiers in Computer Science, 2023)
One traditional model of research on mixed-reality systems, is the laboratory-based experiment where a number of small variants of a user experience are presented to participants under the guidance of an experimenter. This type of experiment can give reliable and generalisable results, but there are arguments for running experiments that are distributed and remote from the laboratory. These include, expanding the participant pool, reaching specific targeted classes of user, access to a variety of equipment, and simply because laboratories might be inaccessible. Further, if the experiment involves multiple simultaneous users, this can exacerbate logistical and safety issues in a laboratory-based setup. However, running experiments out of the laboratory brings a different set of issues into consideration. Here, we present some lessons learned in running distributed and remote mixed-reality experiments. We distil experience from over a dozen such experiments that we have run. We also present how we have distilled some of the tools we have built for our own purposes into examples on our open source Ubiq distributed mixed-reality toolkit.